Male and Female Students’ Discourse Competence at Kalamansig National High School - Reynaldo B. Aranego; Bai Donna S. Aliman; Zaida K. Ulangkaya (Randwick International of Education and Linguistics Science Journal, 2021)
The study aimed to determine the relationship between the oral and written discourse competence of the male and female students of Kalamansig National High School. Specifically, it sought to determine the level of oral and written discourse competence of male and female students in terms of informative, persuasive, and argumentative speeches; to find out if there is significant difference between male and female students’ written and oral discourse competence level in the three parameters; and to find out if there is a significant difference between the oral and written discourse competence in general when classified according to gender. This study used the descriptive-correlation method. The researcher utilized the purposive sampling in determining the seventy (70) Grade 10 performing students of Kalamansig National High School as respondents of the study. The teacher-made communicative written and speaking tests were used as instruments to gauge the male and female student’s written and oral discourse competence. Based on the findings, it was concluded that both male and female students oral and written discourse competence are good. Both group of students need equal attention from the teachers to enhance their speaking and writing skills.